Spinal Cord Parenchyma Vascular Redistribution Underlies Hemodynamic and Neurophysiological Changes at Dynamic Neck Positions in Cervical Spondylotic Myelopathy - Yu, Zhengran; Cheng, Xing; Chen, Jiacheng; Huang, Zhong; He, Shaofu; Hu, Hao; Lin, Sixiong; Zou, Zhiyuan; Huang, Fangli; Chen, Bolin; Wan, Yong; Peng, Xinsheng; et al. (Frontiers in Neuroanatomy, 2021)
Cervical spondylotic myelopathy (CSM) is a degenerative condition of the spine that caused by static and dynamic compression of the spinal cord. However, the mechanisms of motor and somatosensory conduction, as well as pathophysiological changes at dynamic neck positions remain unclear. This study aims to investigate the interplay between neurophysiological and haemodynamic responses at dynamic neck positions in the CSM condition, and the pathological basis behind. We first demonstrated that CSM patients had more severe dynamic motor evoked potentials (DMEPs) deteriorations upon neck flexion than upon extension, while their dynamic somatosensory evoked potentials (DSSEPs) deteriorated to a similar degree upon extension and flexion. We therefore generated a CSM rat model which developed similar neurophysiological characteristics within a 4-week compression period. At 4 weeks-post-injury, these rats presented decreased spinal cord blood flow (SCBF) and oxygen saturation (SO2) at the compression site, especially upon cervical flexion. The dynamic change of DMEPs was significantly correlated with the change in SCBF from neutral to flexion, suggesting they were more sensitive to ischemia compared to DSSEPs. We further demonstrated significant vascular redistribution in the spinal cord parenchyma, caused by angiogenesis mainly concentrated in the anterior part of the compressed site. In addition, the comparative ratio of vascular densities at the anterior and posterior parts of the cord was significantly correlated with the perfusion decrease at neck flexion. This exploratory study revealed that the motor and somatosensory conductive functions of the cervical cord changed differently at dynamic neck positions in CSM conditions. Compared with somatosensory conduction, the motor conductive function of the cervical cord suffered more severe deteriorations upon cervical flexion, which could partly be attributed to its higher susceptibility to spinal cord ischemia. The uneven angiogenesis and vascular distribution in the spinal cord parenchyma might underlie the transient ischemia of the cord at flexion.